Muhammadiyah’s Philosophy of Education - Sulistyono, Tabah (Interdisciplinary Social Studies, 2022)
Background: The basis of this research is first, the existence of a civilization of 'philosophy of life' muhammadiyah education; Second, there is a tajdid movement; third, Muhammadiyah as a pillar of religious thought in Indonesia; fourth, the concept of education that muhammadiyah has built and; Fifth, the philosophy of education that muhammadiyah began to construct is relatively young. This research builds on the question of how the construction of Islamic educational philosophy according to Muhammadiyah. Aim: This research aims to explore aspects of educational philosophy according to Muhammadiyah. Method: This research includes religious research with the point of view of the scope of the research. If based on the type of research including exploratory research with a philosophical approach. Researchers analyzed the data by understanding symbols, giving and digging carefully related to the meaning, essentially the life of symbols, and illuminating interpretations. Findings: The construction of Muhammadiyah Islamic education philosophy begins with the main themes of Muhammadiyah Islamic education. The main themes are the paradigm, nature, policy, and aspects of Muhammadiyah Islamic education. The content of the instruction of Muhammadiyah Islamic education philosophy in the form of muhammadiyah Islamic educational ontology area includes the concept of God, universe, and man, and the epistemological area of Muhammadiyah Islamic education contains the nature of science, curriculum, educators, learners, methods and tools of Islamic education.